Abnormal Endometrial Receptivity and Oxidative Stress in Polycystic Ovary Syndrome - Hongying Shan; Hongying Shan; Renxin Luo; Xuanying Guo; Rong Li; Zhenhong Ye; Tianliu Peng; Fenting Liu; Zi Yang (Frontiers Media S.A., 2022)
Polycystic ovary syndrome (PCOS) is a common endocrine and metabolic disorder in women of childbearing age. Individual heterogeneity is evident, and the prevalence rate ranges between 6 and 15% globally. The prevalence rate of PCOS in Chinese women of childbearing age is 5.6%. The main manifestations are infertility, sparse menstruation, irregular vaginal bleeding, long-term endometrial hyperplasia, and endometrial cancer. PCOS is often associated with hyperandrogenemia, insulin resistance, hyperinsulinemia, obesity, metabolic syndrome, and intestinal flora disorder. Although there have been many studies in the past, the underlying pathophysiological mechanism of the disease is still unclear. Studies have shown that PCOS diseases and related complications are closely related to local oxidative stress imbalance in the endometrium, leading to poor endometrial receptivity and effects on pregnancy. Previous reviews have mainly focused on the abnormal mechanism of ovarian oxidative stress in women with PCOS, while reviews on endometrial receptivity and oxidative stress are relatively insufficient. This study reviews the abnormal cellular and molecular mechanisms of oxidative stress due to comorbidities in women with PCOS, leading to a downregulation of endometrial receptivity.